How Vietnamese Exporting SMEs Translate Green Practices into Export Performance Through Incremental and Radical Green Innovation - Quang-Huy Ngo (SAGE Open)
This research investigates the link between adopting green practices and export performance among exporting SMEs in Vietnam, a booming export-oriented economy. Utilising the natural resource-based view (NRBV), it investigates if green practices directly influence SMEs’ export performance and the mediating role of incremental and radical green innovation in this relationship. The sample consists of 319 Vietnamese exporting SMEs. PLS-SEM was employed for model testing, and Harman’s single-factor test and t-tests were utilised to evaluate potential biases. Green practices positively impact export performance directly and are partially mediated by both types of green innovation. This study applies the NRBV to exporting SMEs in Vietnam to illustrate that adopting green practices, directly and indirectly, enhances export performance through incremental and radical green innovation. Secondly, the study tackles methodological limitations by conceptualising EP as a reflective-formative higher-order construct and concentrating on SMEs. It offers a more refined comprehension of how environmental commitments enhance performance in smaller exporting enterprises. This study integrates the ambidexterity framework into the green innovation literature, demonstrating that the balance of exploitative and explorative actions through green practices’ adoption enhances export performance in both financial and non-financial aspects.